PENGARUH RESTRUKTURISASI KREDIT DAN TINGKAT SUKU BUNGA KREDIT KORPORASI TERHADAP LOAN TO DEPOSIT RATIO PADA PT BANK RAKYAT INDONESIA TBK - Agus Prasetya (POLITEKNIK LP3I JAKARTA, 2022)
The purpose of this study was to determine the effect of Credit Restructuring and Credit Interest Rates Corporate on the Loan to Deposit Ratio at PT Bank Rakyat Indonesia, Tbk. This research is a quantitative study with a sample of secondary data from the Financial Statement of PT Bank Rakyat Indonesia, Tbk in the period 2014 to 2021 obtained from Bank Rakyat Indonesia website. The independent variables in this study are Credit Restructuring and Credit Interest Rates Corporate, while the dependent variable is Loan to Deposit Ratio. Analysis of the data used is multiple linear regression analysis at a significance level of 5%. The results of the study indicate that Credit Restructuring and Interest Rates Credit Corporate have a significant positive effect on the Loan to Deposit partially, while simultaneously have not effect and coefficient determination test has result only 18,7%, the rest is influenced by other variables.Key words: Credit Restructuring, Credit Interest Rates Corporate, and Loan to DepositRatio.